Peran Kepuasan Konsumen dalam Memediasi Pengaruh Kualitas Pelayanan terhadap Kepercayaan Konsumen: (Studi pada Konsumen Kursus Mengemudi Anisa) (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to examine the relationship between service quality and customer trust through customer satisfaction, using the Anisa Driving Course as a case study. A total of 115 respondents were selected through the purposive sampling method, which is a non-probability sampling technique that considers certain characteristics. Data were collected using a questionnaire consisting of three main variables and twenty-three measurement indicators. Data analysis was carried out using the Structural Equation Modelling (SEM) approach using the Partial Least Squares (PLS) method through SmartPLS4 software. The results of the study show that service quality has a positive and significant influence on customer trust. In addition, service quality also has a positive and significant impact on customer satisfaction. Another important finding is that customer satisfaction plays a partial mediator in the relationship between service quality and customer trust. This means that improving the quality of service not only increases satisfaction, but also strengthens customer trust in the company. This study provides a theoretical contribution in understanding the dynamics of the relationship between service variables, as well as practical implications for the managers of the Anisa Driving Course in designing strategies to improve service quality and customer satisfaction. Thus, the results of this research can be the basis for more appropriate decision-making in building customer loyalty and trust in a sustainable manner.